2019
DOI: 10.1002/cncr.32156
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and outcome after first molecular versus overt recurrence in patients with Philadelphia chromosome–positive acute lymphoblastic leukemia included in the ALL Ph08 trial from the Spanish PETHEMA Group

Abstract: Background Disease recurrence occurs in 20% to 40% of adults with Philadelphia chromosome–positive acute lymphoblastic leukemia (Ph+ ALL) who are treated with chemotherapy and tyrosine kinase inhibitors (TKIs). In the current study, the authors report the incidence, treatment, and outcome after first disease recurrence in young and older adults treated in the ALL Ph08 trial (ClinicalTrials.gov identifier NCT01491763). Methods Patients aged 18 to 55 years with de novo Ph+ ALL were treated with imatinib concurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…However, we showed a lower prevalence of ABL KD mutations (41.2% of tested patients) than in adult relapses, detected in 70% of patients 25 . The T315I mutation was the prevalent ABL KD mutation in our cohort, as in others, conferring resistance to imatinib and all second‐generation TKIs, in accordance with reports for adults with Ph + ALL 25–27 . As we did not screen for ABL KD mutations at the initial diagnosis in pediatric cases, we could not determine whether these mutations were pre‐existing and could have been detected at low rates at diagnosis, as described for 20% of adult Ph + ALL relapses 26,28 …”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, we showed a lower prevalence of ABL KD mutations (41.2% of tested patients) than in adult relapses, detected in 70% of patients 25 . The T315I mutation was the prevalent ABL KD mutation in our cohort, as in others, conferring resistance to imatinib and all second‐generation TKIs, in accordance with reports for adults with Ph + ALL 25–27 . As we did not screen for ABL KD mutations at the initial diagnosis in pediatric cases, we could not determine whether these mutations were pre‐existing and could have been detected at low rates at diagnosis, as described for 20% of adult Ph + ALL relapses 26,28 …”
Section: Discussionsupporting
confidence: 82%
“…25 The T315I mutation was the prevalent ABL KD mutation in our cohort, as in others, conferring resistance to imatinib and all second-generation TKIs, in accordance with reports for adults with Ph + ALL. [25][26][27] As we did not screen for ABL KD mutations at the initial diagnosis in pediatric cases, we could not determine whether these mutations were pre-existing and could have been detected at low rates at diagnosis, as described for 20% of adult Ph + ALL relapses. 26,28 Our retrospective study found very promising results in the setting of relapsed Ph + ALL.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Disease persistence or recurrence have been associated with point mutations in the BCR-ABL1 kinase domain (KD). [5][6][7][8][9] Detection of some imatinib-resistant mutations predicts for the efficacy or the inefficacy of the other TKIs. 1 The T315I mutation, in particular, can only be addressed, as yet, by the third-generation TKI ponatinib.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the persistence of detectable minimal residual disease (MRD) is a well‐established negative prognostic factor 2–4 . Disease persistence or recurrence have been associated with point mutations in the BCR‐ABL1 kinase domain (KD) 5–9 . Detection of some imatinib‐resistant mutations predicts for the efficacy or the inefficacy of the other TKIs 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, early detection of relapse and early re‐treatment have also been reported to influence the outcome. Ribera et al from the PETHEMA group reported median DFS and OS of 16.9 (95% CI, not reported) versus 6.3 months (95% CI, 2.1–10.4 months) and median OS 28.7 (95% CI, not available) versus 11.5 months (95% CI, 8.5–14.5 months), respectively 40 . In our study, we observed a similar trend to this report, although we did not find significant differences due to the small number of patients.…”
Section: Discussionmentioning
confidence: 99%